Technological trends: a focus on citizen security - Lasso Cardona, Luis Adrian (Ingeniería Solidaria, 2021)
Introduction: This bibliographic review article is the product of research on new technological trends, focusing on citizen security, carried out at the SIEL research hotbed of the Universidad del Valle-Buga headquarters, Colombia in 2019. Problem: Investigate the new technological trends aimed at the citizen security sector. Objective: Identify the new technological trends in the sector of citizen security, its application in the world and expose the current state in Colombia. Methodology: Documentary review of primary sources of the last 5 years, such as; scientific articles, government pages, laws, press releases and recognized newspapers. Results: Since MinTIC was created in Colombia, in partnership with different government entities, society in general has benefited from projects in areas such as education, health, housing and security. The modernization of control institutions in Colombia is evident being the security sector one of the most advantageous. Conclusion: In general terms, sectors such as technology and education are still lagging behind. As for the security sector, there is no doubt the effort and progress in research and development of new technologies present in the vast majority of government entities. Originality: new technological trends are investigated from the point of view of citizen security in several application scenarios. Limitations: For the most part, the review focuses on aspects of citizen security, indicating very little the social field